Comparison of Topical Analgesic Activity of Mentha piperita Extract with Ethanol Variations Using Hargreaves Test in Mice - Sirilus Deodatus Sawu; Wibowo; Devanus Lahardo (Program Studi Farmasi, Universitas Ma Chung, 2026)
Pain can sometimes significantly disrupt a person's quality of life. Pharmacological pain management, often using synthetic analgesics, remains the primary option, but long-term use can lead to serious side effects and the risk of dependency. Mint leaves (Mentha piperita) are known to contain active compounds such as alkaloids and flavonoids, which have analgesic effects, making them a potential alternative to topical analgesics. This study aims to compare the topical analgesic activity of mint leaf ethanol extract with variations in ethanol solvent concentration (50%, 70%, and 96%) as an extraction solvent using the Hargreaves test method in white mice (Mus musculus). The laboratory experimental research used a posttest-only control group. Mint leaf extract was formulated in the form of a topical gel, then tested using the Hargreaves test method which measures the latency time of pain response to heat stimulation on the soles of the feet of mice. The results showed that the maximum topical analgesic activity occurred at 150 minutes for all three groups of mint leaf ethanol extract gels. The LSD test results showed that the 96% ethanol extract solvent produced significantly higher topical analgesic activity than the 70% and 50% ethanol extracts (p-value <0.05). The concentration of 96% ethanol solvent as a solvent for mint leaf extract produces the most optimal topical analgesic activity based on testing using the Hargreaves test method.